The Impact of Persuasive Communication, Transformational Leaderships, and Work Interest on Work Ethic - Hikmah, Fanzilul; Kirana, Kusuma Chandra; Prayekti, Prayekti (Almana : Jurnal Manajemen dan Bisnis, 2024)
The Yogyakarta City Fire Department is located on Jl. Muja Muju. Umbulharjo, Yogyakarta City, is an implementing element of the government that has the responsibility of assisting the community in handling fires and rescues. In addition to extinguishing fires, firefighters are also trained to carry out evacuations such as accidents, natural disasters, and other emergency evacuations. So the importance of competent and qualified human resources (HR) is needed to support the work ethic and activities so that the mission of the company or an organization can succeed. This study aims to prove and collect empirical evidence that Persuasive Communication, Transformational Leadership, and Work Interest affect the Work Ethic of Employees of the Fire and Rescue Service of Yogyakarta City. By conducting this study, the researcher hopes that the results of this study can be an evaluation in improving the performance and work ethic of the relevant agencies. This type of quantitative research with 67 respondents, using a purposive sampling method. Data was collected using a questionnaire and Likert scale as a measurement. The results of the study partially and simultaneously all variables, namely Persuasive Communication, Transformational Leadership, and Work Interest, have a positive and significant effect on the Work Ethic.